Nationalism or Europeanism? Simmel’s Dilemma - Fitzi, Gregor (Simmel Studies, 2018)
Despite many different research efforts over the past thirty years, one can still attend a conference and learn that Simmel was a radical nationalist who sang in this chorus throughout the First World War. The main references in this respect are the memories of the younger intellectuals of the time like Lukács and Bloch. There is no attempt at assessment – neither of Simmel’s writings nor of his letters. In contrast, the present paper deals with the issue of Simmel’s attitude to the war by focusing on its different periods and by reconstructing the twists and turns that changed it. After an analysis of the reasons that led Lukács and Bloch to claim Simmel’s treason, it describes the unique aspect of Simmel’s early position about the war. In this context, especially the issue of “clearing up” the foreign countries and Simmel’s exchange with Albion Small deserve particular attention. The effects of Simmel’s change of opinion since the spring of 1915 are then reconstructed with reference to his later war writings, especially the anthology on The War and Decisions of the Spirit (1917) as well as his late reflection on the theory of modernity in the essay on “The Conflict of Modern Culture” (1918).